2009
DOI: 10.1097/mcg.0b013e318176ab94
|View full text |Cite
|
Sign up to set email alerts
|

A High-resolution View of Achalasia

Abstract: HRM demonstrates alterations of esophageal motor function in achalasia that are not easily observed with other manometric techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Our findings are also similar to previous adult studies (21). Finally, recent studies with HRM in adults have also demonstrated that some degree of true LES relaxation, although impaired, does exist in patients with achalasia with minimal axial displacement (17,31,32). These results support that the finding of some degree of LES relaxation in conventional manometry is a true phenomenon.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are also similar to previous adult studies (21). Finally, recent studies with HRM in adults have also demonstrated that some degree of true LES relaxation, although impaired, does exist in patients with achalasia with minimal axial displacement (17,31,32). These results support that the finding of some degree of LES relaxation in conventional manometry is a true phenomenon.…”
Section: Discussionsupporting
confidence: 93%
“…Zhang and Diamant observed spontaneous rhythmic contractions in patients with achalasia (Zhang and Diamant, 1994) although this was not observed in another comprehensive study where rhythmic activity was only seen to be swallow-induced (Jee et al, 2009). In recent years, achalasia is classified according to high-resolution manometry features.…”
Section: Discussionmentioning
confidence: 95%
“…Jee et al suggested that they originated in the upper esophageal sphincter (UES) since there they had the highest amplitude (Jee et al, 2009). Zhang and Diamant noted that rhythmic esophageal contractions were not common when the UES did not show them (Zhang and Diamant, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and prevalence of achalasia have been recently reported to be 1.63/100 000 and 10.82/100 000 in Western countries . HRM is a precise tool for the assessment of esophageal motility disorders including achalasia . As a newly introduced manometric method, to date, limited information about the HRM parameters of normal individuals or esophageal motility disorder is available in China.…”
Section: Discussionmentioning
confidence: 99%